Sequence analysis of matK gene of Pueraria Candollei and Butea Superba and the application of PCR-RFLP genetic marker for identification - Woraluk Yodpetch (Chulalongkorn University, 2013)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 2007